2016
DOI: 10.1038/srep27770
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Glycemic Gap is Associated with Adverse Outcomes in Diabetic Patients with Acute Myocardial Infarction

Abstract: Acute hyperglycemia is a frequent finding in patients presenting to the emergency department (ED) with acute myocardial infarction (AMI). The prognostic role of hyperglycemia in diabetic patients with AMI remains controversial. We retrospectively reviewed patients’ medical records to obtain demographic data, clinical presentation, major adverse cardiac events (MACEs), several clinical scores and laboratory data, including the plasma glucose level at initial presentation and HbA1c levels. The glycemic gap, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 86 publications
2
40
1
3
Order By: Relevance
“…Others have reported that relative hyperglycemia at admission to hospital has been associated with poor outcomes in patients with acute illness [ 10 ], stroke [ 9 ], acute myocardial infarction [ 30 , 32 ] and in cardiogenic shock [ 33 ]. In addition to SHR two other measures of relative glycemia have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that relative hyperglycemia at admission to hospital has been associated with poor outcomes in patients with acute illness [ 10 ], stroke [ 9 ], acute myocardial infarction [ 30 , 32 ] and in cardiogenic shock [ 33 ]. In addition to SHR two other measures of relative glycemia have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The “glycemic gap” is the difference between the admission glucose and the estimated average glucose i.e. it is the absolute rather than the relative difference in glucose concentration [ 11 , 32 , 34 ]. Another proposal was for a “glucose concentration-to-HbA1c ratio”, in which the admission glucose is divided by the HbA1c [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is one of the leading causes of death in patients with diabetes [ 1 ]. Hyperglycemia-induced oxidative stress plays a vital role in the development and progression of AMI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation is that patients with diabetes are more adapted to a chronic and premorbid hyperglycemic environment than those patients without diabetes, who may not handle acute hyperglycemia in critical illnesses well [ 15 ]. Another plausible explanation for the inconsistent results is the lack of consideration of patients’ premorbid hyperglycemia in many reports, especially in patients with diabetes [ 16 , 17 , 18 ]. Furthermore, SIH and DH are not mutually exclusive entities, as DH patients may have some degree of stress response, invoking their hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…In an international multicenter study, the long-term average glucose levels were estimated by converting HbA1c values into A1c-derived average glucose (ADAG), using the equation, ADAG = ((28.7 × HbA1c) − 46.7) [ 21 , 22 ], which presented a strong correlation between HbA1c and mean plasma glucose levels in the preceding 3 months. Some glycemic variables, after adjusting for ADAG, are useful in the assessment of adverse outcomes in patients with diabetes [ 16 , 17 , 18 ]. For example, glycemic gap, the admission glucose level minus ADAG, indicates elevated glucose levels in diabetes patients with critical illnesses.…”
Section: Introductionmentioning
confidence: 99%